Designing Reading Side as Educational Application for Senior High School Learners - Rohmat Hidayat; Ulfa Wulan Agustina; Muchamad Rahman Bagus Tohari (Journey: Journal of English Language and Pedagogy, 2025)
The utilization of ICT (Information and Communication Technology) based learning media has become a significant factor in enhancing the usefulness and efficiency of the learning process. The objective of this research is to develop R-SIDE applications and to test the usefulness of it for use by senior high school students. The researchers employed the research and development (R&D) method. This method comprises five stages: analysis, design, development, implementation, and evaluation. The data were collected using two instruments: observation and questionnaire. Prior to implementation, the R-SIDE applications were validated by four experts, comprising two material experts and two media experts. The material expert validators indicated a level of agreement with the items in the "Agree" category, with a mean score of 80.00. Moreover, the media expert validators provided scores of 78 in the "Agree" category and 91.7 in the "Strongly Agree" category. A trial implementation was conducted on 25 students at MAAl Ihsan Tembelang Jombang, with the results of the questionnaires indicating an average score of 85.5, classified as "very good." Based on these findings, it can be concluded that the R-SIDE application is a viable method for engaging students in English learning, particularly in the context of reading skills.